Lipoprotein(a) and Cardiovascular Disease: Evidence, Recommendations and Emerging Therapies - Wong, Nathan D (Scripta Medica, 2025)
Lipoprotein(a) (Lp[a]) is a low-density lipoprotein (LDL) like particle which has atherogenic, proinflammatory and prothrombotic properties. Elevated in approximately 1 in 5 persons, increased levels of Lp(a) have been shown by epidemiological, genome wide association studies and Mendelian randomisation studies to be a causal factor for atherosclerotic cardiovascular disease (ASCVD). Lp(a) is primary genetically determined and is more atherogenic than LDL. Current recommendations from Europe, Canada, India and the United States recommend testing at least once in all adults. Persons found to have elevated levels (eg, > 50 mg/dL or > 125 nmol/L) are recommended for more intensive risk factor management, including further LDL-C lowering. With lipoprotein apheresis the only currently approved therapy for lowering Lp(a), several newer antisense oligonucleotide (ASO) and small interfering RNA (siRNA) therapies are in development and may soon provide additional therapeutic options for persons with elevated Lp(a). Several cardiovascular outcomes trials are underway involving these new therapies with the first to read out in 2026. Lp(a) is a key risk factor that warrants greater attention for testing, with further efforts to reduce ASCVD in those found to have elevated levels, especially in higher risk persons.
Keywords: Cardiovascular diseases; Lipoproteins; LDL; Atherosclerosis